Opportunities and alternatives of modern radiation oncology and surgery for the management of resectable brain metastases - Diehl, Christian; Giordano, Frank Anton; Grosu, Anca-Ligia; Ille, Sebastian; Kahl, Klaus-Henning; Onken, Julia; Rieken, Stefan; Sarria, Gustavo R.; Shiban, Ehab; Wagner, Arthur; Beck, Jürgen; Brehmer, Stefanie; et al. (Cancers, 2023)
Postsurgical radiotherapy (RT) has been early proven to prevent local tumor recurrence, initially performed with whole brain RT (WBRT). Subsequent to disadvantageous cognitive sequalae for the patient and the broad distribution of modern linear accelerators, focal irradiation of the tumor has omitted WBRT in most cases. In many studies, the effectiveness of local RT of the resection cavity, either as single-fraction stereotactic radiosurgery (SRS) or hypo-fractionated stereotactic RT (hFSRT), has been demonstrated to be effective and safe. However, whereas prospective high-level incidence is still lacking on which dose and fractionation scheme is the best choice for the patient, further ablative techniques have come into play. Neoadjuvant SRS (N-SRS) prior to resection combines straightforward target delineation with an accelerated post-surgical phase, allowing an earlier start of systemic treatment or rehabilitation as indicated. In addition, low-energy intraoperative RT (IORT) on the surgical bed has been introduced as another alternative to external beam RT, offering sterilization of the cavity surface with steep dose gradients towards the healthy brain. This consensus paper summarizes current local treatment strategies for resectable brain metastases regarding available data and patient-centered decision-making.
Gesehen am 18.07.2024